2008
DOI: 10.1007/s11255-008-9429-5
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life after hand-assisted laparoscopic and open radical nephrectomies of renal cell carcinoma

Abstract: The results showed that hand-assisted laparoscopic surgery is a minimally invasive surgical technique for RCC offering earlier recovery and similar long-term HRQOL compared with open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…Quality of life (QOL) was set to 1 for patients without a tumor. Likewise, based on previous literature, QOL for patients with a localized tumor was set to 0.97, as surgery and possible complications lead to a reduction of QOL [18]. In accordance with literature, the QOL of patients with a metastasized tumor was set to 0.67 [4].…”
Section: Costs and Utilitiesmentioning
confidence: 99%
“…Quality of life (QOL) was set to 1 for patients without a tumor. Likewise, based on previous literature, QOL for patients with a localized tumor was set to 0.97, as surgery and possible complications lead to a reduction of QOL [18]. In accordance with literature, the QOL of patients with a metastasized tumor was set to 0.67 [4].…”
Section: Costs and Utilitiesmentioning
confidence: 99%
“…Clinical studies have shown clear benefits in regard to earlier return to activities, resumption of oral intake, and other peri-operative outcomes with minimally invasive surgery 5, 11 . Our results show that these approaches have measurable short-term patient-reported QOL benefits, but the differences disappear after a few months.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic radical nephrectomy is performed commonly at both community and academic centers, even at the risk of overutilization for tumors which may be amenable to nephron-sparing surgery 9, 10 . A small retrospective study of patients 1 year after undergoing laparoscopic versus open radical nephrectomy showed no significant difference in QOL 11 , while a prospective study of the same procedures noted QOL benefits among the laparoscopic group 12 .…”
mentioning
confidence: 96%
“…Minimally invasive techniques for extirpative renal surgery have emerged as a standard of care, oVering oncologic outcomes equivalent to open procedures while at the same time aVording the patient reduced recovery times and improved cosmesis [1][2][3][4][5][6][7][8][9][10]. However, these techniques are technically challenging, requiring considerable surgical skill and proper surgical planning.…”
Section: Introductionmentioning
confidence: 99%